Self-autonomy and psychological identity among Anbar University students - Al-Falahi, Hassan Hamoud; Al-Akidi, Muayad Dhari (Arab Journal for Sciences and Research Publishing, 2017)
The aim of the current research is to identify the level of autonomy at Anbar University students and the significance of statistical differences in the level of independence of the sample depending on the variables of specialization (scientific/ humanist), genre (male/ female) and the level of psychological identity among university students and the significance of statistical differences in the psychological level of identity depending on variables specialization (scientific/ humanistic), kind (male/ female), and the relationship between psychological autonomy and identity among university students.The researchers adopted steps of descriptive approach to achieve the goals of their research, has been selected sample of random stratified way, reaching 120 students in Anbar University for the academic year (2015-2016) and adopted the researchers Adata Search: first autonomy measure may be (36) paragraph and identified alternatives with four alternatives, and the second: A measure of psychological identity may be (52) paragraph alternatives pentagonal. Also check the two researchers from the standard characteristics of the two measures and of honesty and consistency has been applied to the two scales on the sample after the data by statistical means derived treatment (Altaia test (T-test) for one sample, the test Altaia (T-test) for two independent samples, Pearson correlation coefficient, the equation Alvakronbach , Kai box) the results showed that college students have autonomy highly statistically significant, and there are no statistically significant differences between the university students in the level of autonomy due to the variable specialization (scientific/ humanist), gender (male/ female), and university students have psychological identity function and there is no statistically significant differences between the university students in the psychological identity due to the variable level of specialization (scientific/ humanistic), kind (male/ female) and the results showed a lack of correlation between psychological autonomy and identity.